ENGLISH TEACHING MATERIALS AND CORPUS LINGUISTICS - Lima, Thereza Cristina de Souza; Ritter, Rejane Koppe Rolim (Kur'yt'yba - Revista Multidisciplinar de Educação e Ciência, 2023)
The purpose of the present article is to provide language teachers and students, as well as those interested in linguistic research, with a general overview about corpus-based materials, which many scholars consider the latest tendency in English language teaching. Based on Corpus Linguistics research, such materials intend to meet the needs of a new generation to whom English is essential, as it is part of their lives. Starting with an overview of the learning clientele profile, the text then offers a simplified definition of Corpus Linguistics and its object of study, the language use, presents ashort historical background, focuses on the use of its findings by material developers and finally states how learners can benefit from this approach.